2015
DOI: 10.1021/acs.macromol.5b00679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Effects of Silica Nanoparticles on (80/20) PP/PS Blends via Nonlinear Rheological Properties from Fourier Transform Rheology

Abstract: Effects of silica nanoparticles with different natures (hydrophilicity and hydrophobicity) on (80/20) PP/PS blends were investigated via linear and nonlinear rheological properties. The hydrophilic silica nanoparticle was fumed silica OX50 while the two hydrophobic ones were precipitated silica D17 and fumed silica R202. SEM images revealed that hydrophilic OX50 could not improve morphological properties of the blends. On the other hand, the two hydrophobic silica nanoparticles (R202 and D17) improved morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 37 publications
8
71
0
Order By: Relevance
“…As a result, the rheological properties of the blend changed slightly, most likely because of the hydrodynamic (volumetric) effects of particles rather than them acting as morphology modifiers. Salehiyan et al . reported similar results when hydrophilic particles (Cloisite30B, untreated CNa + clays, and OX50 fumed silica) were added to 80/20 PP/PS blends: they mostly localized inside the PS droplets.…”
Section: Resultsmentioning
confidence: 64%
“…As a result, the rheological properties of the blend changed slightly, most likely because of the hydrodynamic (volumetric) effects of particles rather than them acting as morphology modifiers. Salehiyan et al . reported similar results when hydrophilic particles (Cloisite30B, untreated CNa + clays, and OX50 fumed silica) were added to 80/20 PP/PS blends: they mostly localized inside the PS droplets.…”
Section: Resultsmentioning
confidence: 64%
“…As a result, there was a greater interaction between these silica particles and the minor BHAS phase than the PBSA matrix, which lead to limited interactions per unit volume, thereby, slightly increasing the viscosity and storage modulus with increasing silica content, but with no significant improvement with the changes in the screw speed. Similarly, other researchers observed less marked improvement in storage modulus with the addition of hydrophilic silica particles to the PP/PS (80/20) blends; instead observing that the hydrophilic silica particles were jammed inside the dispersed PS phase, which resulted in large particle clusters that led to no significant improvement in morphology, thus, to less effective improvements in rheological properties . Clearly, there was a relationship between the rheological behavior of composites and the localization of silica particles in the PBSA/BHAS blends.…”
Section: Resultsmentioning
confidence: 90%
“…This indicates that the highly agglomerated microsilica particles in the PBSA matrix result in inefficient improvement of droplet breakup and with the decrease in the size of the agglomerate, dispersion improves, leading to the improvement in droplet breakup. In a similar study, Salehiyan et al studied the effects of silica nanoparticles on PP/PS blends and observed that hydrophilic silica nanoparticles did not improve the morphological properties of PP/PS blends. They also discovered that the aggregated silica nanoparticles were located inside the dispersed PS phase, which led to the formation of irregular droplet shapes as well as coexistence of large and small droplets, indicating inefficient suppression of coalescence by hydrophilic silica particles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations